2013
DOI: 10.1175/jas-d-12-0341.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Poleward Motion of Midlatitude Cyclones in a Baroclinic Meandering Jet

Abstract: International audienceThe motion of surface depressions evolving in a background meandering baroclinic jet is investigated using a two-layer quasigeostrophic model on a beta plane. Synoptic-scale finite-amplitude cyclones are initialized in the lower and upper layer to the south of the jet in a configuration favorable to their baroclinic interaction. The lower-layer cyclone is shown to move across the jet axis from its warm-air to cold-air side. It is the presence of a poleward-oriented barotropic potential vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 60 publications
3
25
0
Order By: Relevance
“…The result above implies the opposite. The above is in fact consistent with the recent baroclinic studies of Riviére et al (2012) and Oruba et al (2013), who found that a stronger barotropic PV gradient was linked to more rapid poleward translation. As we noted in the paper, our numerical results were inconclusive with regards to changes in the PV gradient.…”
supporting
confidence: 92%
“…The result above implies the opposite. The above is in fact consistent with the recent baroclinic studies of Riviére et al (2012) and Oruba et al (2013), who found that a stronger barotropic PV gradient was linked to more rapid poleward translation. As we noted in the paper, our numerical results were inconclusive with regards to changes in the PV gradient.…”
supporting
confidence: 92%
“…A decomposition of this term to its different components (not shown) shows that it is the zonal flow that is responsible for the eastward advection of the perturbation PV, while the nonlinear advection terms are those responsible for the poleward tendency [Tamarin and Kaspi, 2016]. This poleward advection is associated with lower level winds induced by PV at upper levels [Gilet et al, 2009;Oruba et al, 2013;Coronel et al, 2015;Tamarin and Kaspi, 2016]. In the PV perspective, cyclogenesis is described as the mutual amplification of a positive low-level PV anomaly, associated with the cyclone, and a positive upper level PV anomaly to its west [Bretherton, 1966;Hoskins et al, 1985].…”
Section: Poleward Motion Of Cyclonesmentioning
confidence: 99%
“…The case c = 0 consists of when the jet disappears; there are then square cells of alternating vorticity (the Taylor-Green flow [52]). Here, the generic situation of when −1 < c < 0 is the focus; Figure 1 has been produced with c = −0.1868 (associated with realistic parameters for a typical atmospheric midlatitude cyclone as reported by Oruba et al [9], to be discussed in detail later). The dimensional wavenumbers (k 0 , l 0 ) are associated with the zonal and meridional reciprocal lengthscales of the eddy.…”
Section: Rossby Wavesmentioning
confidence: 99%
“…The parameters A and β do not independently affect the flux. For numerical work, parameters associated with a midlatitude cyclone evolving in a background meandering atmospheric jet as studied by Oruba et al [9] will be used. Their Table 2 and Figure 5 indicate the values [9] f 0 = 10…”
Section: Optimal Wavenumbersmentioning
confidence: 99%